O pewnym zagadnieniu rozkładów temperatury przy stochastycznych źródłach ciepła w pręcie - Chmielniak, T.; Czogala, E. (Engineering Transactions, 1969)
The subject of analysis is the random stationary temperature field of one-dimensional problem under the assumption of external and internal stochastic sources of heat. The correlation method has been employed to determine the moments of the first and the second order of the sought quantity. (temperature in the rod) with given stochastic excitations (internal heat sources, ambient temperature) Correlation functions and temperature distribution dispersions in the rod have been determined for the given spectrum densities of excitations. The presented numerical example illustrates the method of proceeding under the assumption of a constant spectrum density (white noise) of external and internal excitation. The computations have been performed on a UMC-1 computer in Computer Centre of Silesia Polytechnics.